Manothermosonication: Inactivation of Escherichia coli and Staphylococcus aureus. (April 2019) - Chantapakul, Thunthacha; Lv, Ruiling; Wang, Wenjun; Chummalee, Watcharapong; Ding, Tian; Liu, Donghong
Abstract: Manothermosonication (MTS) has been one of the key alternatives to current pasteurization techniques. This study evaluates the effectiveness of the MTS system in the inactivation of two opposite gram-stained bacteria: E. coli ATCC 25922 and S. aureus ATCC 25923. Samples were treated with different conditions, including mild heat (T, 50 °C, 100 kPa), sonication (US, 30 °C, 100 kPa), thermosonication (TS, 50 °C, 100 kPa), manosonication (MS, 30 °C, 400 kPa), and manothermosonication (MTS, 50 °C, 400 kPa) in pulse mode for precise temperature control. After 5 min, the viability of E. coli and S. aureus treated with MTS decreased by 6.25 and 4.55 log CFU/mL, and the maximum decrease in non-linear Biphasic decimal reduction (D-value) of the sensitive population was 91.35% and 94.24%, respectively. Since pressurized ultrasound generated excess heat of up to 0.88 °C/sec, an inactivation experiment employing such heat resulted in minimal linear D-values of 0.17 ( E. coli ) min and 0.18 min ( S. aureus ) with power intensity of 3.69 Watt/mL thermally or 14.29 Watt/mL electrically. All experiments indicated that gram-positive S. aureus was more resistant to sonication than gram-negative E. coli, but the lethality rate became more comparable with more violent cavitation. Highlights: Detailed MTS laboratory scale equipment was described. Bacteria inactivation kinetic follows the Biphasic model with two sub-populations. Pressurized sonication and heat cooperate together as a synergistic effect. Optimal inactivation for E. coli and S. aureus revealed less than 0.2 min D-values. MTS exerted disruptions on both outer membrane and cytoplasmic components of bacteria.